Performance Evaluation of Hypervisors: A Comprehensive Benchmarking Study on VMware, Xen, and KVM - Satalino, Michael; Wu, Hao; Pang, Yulei (2026 3rd International Conference on Computer and Multimedia Technology (ICCMT), 2026)
This research presents a comparative performance analysis of three prominent hypervisor architectures—KVM, Xen, and VMware Workstation—to evaluate their scalability and resource efficiency under increasing virtual machine (VM) densities. Utilizing a standardized benchmarking framework, this study quantifies performance regressing across CPU throughput (GFLOPS), memory bandwidth, disk I/O, and initialization latency. The experiment results reveal that architectural design significantly dictates scalability limits: KVM’s kernel-integrated Type-1 model achieved the highest efficiency, maintaining a near-native CPU baseline and superior I/O resilience at peak density. In contrast, Xen’s microkernel architecture demonstrated stable but lower throughput due to Domain 0 (Dom0) management overhead, while VMware’s Type-2 hosted model exhibited the most acute performance degradation. These results demonstrate that while hosted hypervisors are suitable for low-density personal use, kernel-level integration is a mechanical necessity for maintaining performance in high-concurrency server environments. This work provides a reproducible methodology and critical data for system architects and researchers seeking to optimize resource orchestration in distributed and parallel systems.
Keywords: Central Processing Unit; Cloud Computing; Hardware; Hypervisor Benchmarking; Information rates; KVM; Management information base; Measurement; Memory; Performance Evaluation; Throughput; VMware; Virtual machine monitors; Virtual machines; Virtualization; Xen; dept.csc; dept.mat

Hypergeometric decomposition of Delsarte K3 pencils - Davis, Rachel; Dukes, Jessamyn; Ribeiro, Thais; Orvis, Eli; Salerno, Adriana; Sturman, Leah; Whitcher, Ursula (Research in the Mathematical Sciences, 2026)
Abstract We study five pencils of projective quartic Delsarte K3 surfaces. Over finite fields, we give explicit formulas for the point counts of each family, written in terms of hypergeometric sums. Over the complex numbers, we match the periods of the corresponding family with hypergeometric differential operators and series. We also obtain a decomposition of the incomplete L -function of each pencil in terms of hypergeometric L -series and Dedekind zeta functions. This gives an explicit description of the hypergeometric motives geometrically realized by each pencil.
Keywords: Basic hypergeometric series; Generalized hypergeometric function; Hypergeometric distribution; Hypergeometric function; Pencil (optics); Point (geometry); Quartic function; dept.mat

MaPP Challenge : Giving a Taste of Contemporary Mathematics Research to Secondary Students in a Puzzle‑Based Outreach Program - Lee, Younhee; Carrigan, Braxton; Clontz, Steven; Couch, P.; Jones, Cadavious; Noble, Abby; Owens, Andrew; Pang, Yulei (Mathematics Outreach: Examples and Impact from Across the Globe, 2026)
Keywords: Community‑driven; Event (particle physics); Focus (optics); Focus group; Outreach; Perception; Taste; contemporary mathematics; dept.mat; fostering positive mathematical identity; inclusive mathematical outreach program; puzzle‑ based outreach

Toward Resolving Kang and Park’s Generalization of the Alder–Andrews Theorem - Sturman, Leah; Swisher, Holly (La Matematica, 2026)
Keywords: Alder–Andrews theorem; Alder’s conjecture; Conjecture; Generalization; Inequality; Kang-Park conjecture; Partition (number theory); Rogers–Ramanujan identities; Type (biology); d-distinct partitions; dept.mat